2018
DOI: 10.1007/s00204-018-2162-7
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome b 5 impacts on cytochrome P450-mediated metabolism of benzo[a]pyrene and its DNA adduct formation: studies in hepatic cytochrome b 5 /P450 reductase null (HBRN) mice

Abstract: Benzo[a]pyrene (BaP) is an environmental pollutant that, based on evidence largely from in vitro studies, exerts its genotoxic effects after metabolic activation by cytochrome P450s. In the present study, Hepatic Reductase Null (HRN) and Hepatic Cytochrome b5/P450 Reductase Null (HBRN) mice have been used to study the role of P450s in the metabolic activation of BaP in vivo. In HRN mice, cytochrome P450 oxidoreductase (POR), the electron donor to P450, is deleted specifically in hepatocytes. In HBRN mice the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 62 publications
1
27
0
Order By: Relevance
“…Tissue distribution of this SULT is restricted mainly to the liver and bladder ( 60 ), although low amounts have been detected in another human colon carcinoma cell line (Caco-2) ( 61 ) and in some human colon samples ( 36 ). Furthermore, the microsomal enzyme NADPH:P450 oxidoreductase (POR), which is the electron donor of CYP enzymes ( 62 ), is also capable of activating 3-NBA through simple nitroreduction in cell-free experimental systems ( 56 ). However, using the Hepatic Reductase Null mouse model, in which POR is specifically deleted in hepatocytes, it was shown that bioactivation of 3-NBA is dependent predominantly on cytosolic NQO1 rather than microsomal POR ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tissue distribution of this SULT is restricted mainly to the liver and bladder ( 60 ), although low amounts have been detected in another human colon carcinoma cell line (Caco-2) ( 61 ) and in some human colon samples ( 36 ). Furthermore, the microsomal enzyme NADPH:P450 oxidoreductase (POR), which is the electron donor of CYP enzymes ( 62 ), is also capable of activating 3-NBA through simple nitroreduction in cell-free experimental systems ( 56 ). However, using the Hepatic Reductase Null mouse model, in which POR is specifically deleted in hepatocytes, it was shown that bioactivation of 3-NBA is dependent predominantly on cytosolic NQO1 rather than microsomal POR ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic microsomes from ellipticine-treated mice were isolated as described previously (Reed et al, 2018). Microsomes were isolated from 4 pooled livers of each mouse model.…”
Section: Methodsmentioning
confidence: 99%
“…POR enzyme activity was determined as described previously (Arlt et al, 2003). Western blotting analysis using 4–12% Bis-Tris gradient gels and sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) were carried out as described previously (Reed et al, 2018). After migration the proteins were transferred onto polyvinylidene difluoride (PVDF) membranes and the following primary antibodies were used: anti-Cyp1a1 1:1000 (sc-20,772 (H-70), Santa Cruz Biotech); anti-Cyp3a 1:20000 (ab3572, Abcam); anti-Por 1:1000 (ab39995, Abcam), anti-Cyb5 1:750 (ab69801, Abcam); and anti-Cyb5R 1:1000 (ABIN453978, antibodies-online.com).…”
Section: Methodsmentioning
confidence: 99%
“…The nuclease P 1 enrichment version of the thin-layer chromatography 32 P-postlabelling assay was used to determine bulky DNA adduct formation. The procedure was performed essentially as described,10 with minor modifications. All samples were analysed blind and in duplicate.…”
Section: Methodsmentioning
confidence: 99%
“…PAHs induce cytochrome P450 monooxygenases, which are key metabolising enzymes in PAH-bioactivation to diol-epoxides, radical cations and o-quinones 10. These reactive metabolites can directly affect DNA by forming adducts and initiating carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%